Crossed carbon skeleton enhances the electrochemical performance of porous silicon nanowires for lithium ion battery anode. (1st August 2018) - Zhang, Fangfang; Wan, Liu; Chen, Jiangtao; Li, Xiaocheng; Yan, Xingbin
Abstract: As a most promising anode candidate, silicon has the shortcomings of low electron conductivity and high volume expansion of 300%, hindering its applications in lithium ion batteries (LIBs). In this study, one-dimension porous silicon nanowires (pSi-NWs) were prepared through a simple metal-assisted chemical etching process by using metallurgical silicon as raw material. To consolidate the structural integrity of pSi-NWs, a crossed carbon skeleton (c-Cs) was introduced into pSi-NWs via in-situ polymerization and carbonization process. The resultant pSi-NWs@c-Cs composite delivered the high capacity of 1253 mAh g −1 with good cycling stability as well as the notable rate capability (476 mAh g −1 at 4 A g −1 ), much superior to those of pSi-NWs and pSi-NWs@reduced graphene oxide composite. The enhanced electrochemical performance of pSi-NWs@c-Cs composite is attributed to the crossed carbon skeleton in constructing the advanced Si/C interface to more effectively improve the electron conductivity of pSi-NWs and acting as the protective shell to keep the structure integrity of pSi-NWs. As the additive of commercial graphite anode, 28% of capacity augment (460 mAh g −1 at 0.2 A g −1 ) was realized by adding 20 wt% of pSi-NWs@c-Cs composite into graphite, demonstrating its promising applications in LIBs.